Endomyocardial fibrosis associated with mansoni schistosomiasis - Carneiro,Renata de Carvalho Bicalho (2011)
Endomyocardial fibrosis (EMF) is a neglected tropical disease that affects millions of people worldwide. EMF is the most common cause of restrictive cardiomyopathy, caused by deposition of fibrous tissue on endocardial surfaces. EMF is a major cause of death in areas where it is endemic, but the pathogenesis of the disease is poorly understood. Schistosomiasis mansoni is a parasitic disease endemic in Brazil, where EMF has also been described. The association between EMF and schistosomiasis has been suggested in various publications, seeking a possible correlation between endocardial and periportal fibroses. This report describes a case of EMF associated with schistosomiasis.